The actor and the character explorations in the psychology of transformative acting (Abingdon, Oxon New York, NY Routledge, 2019)
"What are the physical and psychological processes which enable actors to create characters so different from themselves? To understand this unique phenomenon, Vladimir Mirodan provides both a historical overview of the evolution of notions of 'character' in Western theatre and a stunning contemporary analysis of the theoretical implications of transformative acting. The Actor and the Character speaks not only to academics and students, but contributes to current lively academic debates around character. Mirodan boldly re-examines some of the fundamental assumptions of actor training and some basic tenets of theatre practice to ask: What happens when one of us 'becomes somebody else'?"--Provided by publisher.
An independent character -- A brief history of ... type -- Friends for life: character and literary criticism -- The drama of no character -- Constructing the character -- Psychologies: I. Trait, type and temperament -- Psychologies: II. Conflict and energy -- Psychologies: III. Character on the couch -- Imagining the character -- Experiencing the character -- Deception, self-deception and the transformative actor.
Includes bibliographical references and index.
Keywords: Acting -- Psychological aspects